PENERAPAN PENDEKATAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KREATIVITAS SISWA PADA PEMBELAJARAN IPS KELAS IV SEKOLAH DASAR - Oswaldayah Mertha Romadona; Arifin Maksum; Ajat Sudrajat (ITB AAS Indonesia Surakarta, 2021)
This research aims to examine whether Problem Based Learning approach is able to increase the creativity of fourth grade elementary school students.? (2) How to improve the process of student creativity through problem based learning in grade IV elementary school students?. This is a qualitative research in a Classroom Action Research (CAR) type. This research was conducted on the four grade learners at Public Elementary School Bogor city, West Java Province. The result shows that: First, learning outcomes or conceptual understanding on the use of natural resources in Indonesia, for Fourth grade, semester II before applying the Problem Based Learning (PBL) Learning Model in Social Science Subjects (IPS) is still low. Second, the application of the PBL Model in point one is carried out in two cycles. Third, Student learning outcomes in point one after implementing the Problem Based Learning (PBL) Learning Model were proven to increase the students’ creativity in social studies learning, for example in cycle I, the average student learning outcomes were 68, then in Cycle II it increased to 78. Keywords: improvement, student creativity, social Sciences, PBL.